1999
DOI: 10.1016/s1357-2725(99)00032-1
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen

Abstract: Fibrinogen is a blood-borne glycoprotein comprised of three pairs of nonidentical polypeptide chains. Following vascular injury, fibrinogen is cleaved by thrombin to form fibrin which is the most abundant component of blood clots. As well as controlling blood loss at sites of tissue damage, other properties of fibrinogen have recently been discovered. For example, various cleavage products of fibrinogen and fibrin, released during coagulation and fibrinolysis, respectively, regulate cell adhesion and spreading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
236
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(242 citation statements)
references
References 13 publications
5
236
0
1
Order By: Relevance
“…They consist of 2 symmetric half molecules, each containing a set of 3 different polypeptide chains termed A␣, B␤, and ␥. 1,6 The 3 chains are encoded by 3 separate genes, fibrinogen alpha (FGA), fibrinogen beta (FGB), and fibrinogen gamma (FGG), clustered in a region of approximately 50 kb on chromosome 4q31.3. The FGG gene contains 10 exons and is oriented in tandem with the FGA gene, which contains 6 exons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They consist of 2 symmetric half molecules, each containing a set of 3 different polypeptide chains termed A␣, B␤, and ␥. 1,6 The 3 chains are encoded by 3 separate genes, fibrinogen alpha (FGA), fibrinogen beta (FGB), and fibrinogen gamma (FGG), clustered in a region of approximately 50 kb on chromosome 4q31.3. The FGG gene contains 10 exons and is oriented in tandem with the FGA gene, which contains 6 exons.…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant form of the ␥ chain, ␥〈, consists of 411 amino acid residues, whereas the variant ␥Ј (␥B) chain (7%-15% of ␥ chains) 10 contains 427 amino acid residues. 6 Abnormalities of fibrinogen have been reported to affect the risk for deep venous thrombosis. In a large case-control study, elevated levels of plasma fibrinogen were found to increase the risk for thrombosis, primarily in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…As well as providing essential hemostasis and support for cell migration, the fibrin matrix is thought to play a much broader physiological role during the repair process. 1,2 For instance, fibrin(ogen) is centrally involved in platelet aggregation and activation, its cleavage fragments have been identified as key molecular effectors of the fibroproliferative response and it acts as a storage reservoir for a number of important growth factors, proteases, and their inhibitors. During the repair process, the fibrin-rich matrix is degraded and replaced by a more permanent fibrous matrix predominately composed of collagen.…”
mentioning
confidence: 99%
“…Bước cuối cùng thông thường của các hệ thống làm đông máu bên ngoài và nội tại liên quan đến việc kích hoạt yếu tố X thành Xa và sau đó kích hoạt prothrombin thành thrombin. Thrombin thúc đẩy sự phân cắt fibrinogen thành fibrin monome liên kết với nhau, với sự hỗ trợ của yếu tố XIII, để tạo thành cục máu đông [7]. Nồng độ fibrinogen trong huyết thanh thông thường từ 1,5-2,77 g/l, tùy thuộc vào phương pháp đo sử dụng.…”
Section: +unclassified